Removal of anionic phenol red from water solution in the batch system by using N,N-dimethylacrylamide and 3-acrlylamidopropil-trimethyl ammonium chloride-based polymeric hydrogels - Tuba Erşen Dudu (MANAS: Journal of Engineering)
p(DMAAm-co-APTMACl) based hydrogels were synthesized at different molar ratios by the redox polymerization technique using N,N-Dimethylacrylamide (DMAAm) and 3-acrlylamidopropil-trimethyl ammonium chloride (APTMACl) monomers and a crosslinker. In this study was aimed to improve the swelling properties and dye sorption of the prepared hydrogels. The balance swelling values of hydrogels were determined by the gravimetric method in deionized water and different pH values, and their structural characterizations were carried out by Fourier transform infrared spectroscopy (FT-IR) and thermal gravimetric analysis (TGA) techniques. Sorption efficiencies and sorption capacities of the synthesized hydrogels were determined using aqueous solutions containing phenol red dye at 25°C. In sorption studies, the effects of different concentrations (5-50 ppm) and different pH values (2-12) on sorption were examined. When the swelling analysis in deionized water was examined, it was determined that there was a significant increase in the balance swelling value of p(DMAAm-co-APTMACl) based hydrogel as the mole ratio of APTMACl increased. In addition, the increase in the molar ratio of APTMACl was found to increase the phenol red dye sorption capacity and removal percentage. It was observed that p(DMAAm-co-APTMACl) (2:8) based hydrogel had a maximum sorption capacity in the range of 5-50 ppm and reached 122.2 mg/g. Experimental data showed that the synthesized p (DMAAm-co-APTMACl) based hydrogel was effective in removing dye from wastewater and could be increased of dyestuff removal by synthesizing at different molar ratios.